Glycerol Impact on Human and Bovine Erythrocytes Under Hypertonic Shock - Nipot, Olena Ye.; Yershova, Natalya A.; Shapkina, Olga O.; Yershov, Sergiy S.; Kuchkov, Vadim M. (Problems of Cryobiology and Cryomedicine, 2019)
Here, we have studied the impact of preliminary incubation of human and bovine erythrocytes in glycerol solutions on their sensitivity to hypertonic shock. The cell damage was shown to significantly reduce with increasing the glycerol concentration. The ranges of a sharp change in human and bovine cell sensitivity were from 0.1 to 0.5 and 0.5 to 1 M, respectively. A change in incubation time with glycerol from 1 to 10 min resulted in sensitivity decrease to hypertonic shock for both mammalian species, but the curves of dependence were different. A damaging effect of hypertonic shock increased with temperature rise from 0 up to 10°C for human erythrocytes and from 0 to 25°C for bovine ones. Preliminary erythrocyte incubation with glycerol entailed a decreased hypertonic damage of erythrocytes at all the studied temperatures for human cells and at those above 5°C for bovine cells. Our findings and the reported data review suggested about a different protective mechanism for human and bovine erythrocytes using glycerol under hypertonic shock conditions. Probl Cryobiol Cryomed 2019; 29(3):199–205.